Busbar technology development for the HL-LHC inner triplet magnets. (June 2020) - Tsolakis, E.; Favier, L.; Principe, R.; Prin, H.; Meuter, F.; Scheuerlein, C.
Abstract: The busbars for the HL-LHC magnets are made of Nb-Ti/Cu conductor, the insulation system, and the auxiliary equipment to align the busbars with respect to the magnet coldmasses. This paper presents design options concerning the integration of the busbars inside the coldmass with a fixed point, and a reinforced insulation system for the flexible busbar part using thin PEEK tubes. Prototype splices for interconnecting Nb3Sn and Nb-Ti Rutherford cables, and round and flat 18 kA Nb-Ti cable have been produced and first test results are presented.